Microclimate limits thermal behaviour favourable to disease control in a nocturnal amphibian. (6th October 2020) - Beukema, Wouter; Pasmans, Frank; Van Praet, Sarah; Ferri‐Yáñez, Francisco; Kelly, Moira; Laking, Alexandra E.; Erens, Jesse; Speybroeck, Jeroen; Verheyen, Kris; Lens, Luc; Martel, An
Abstract: While epizootics increasingly affect wildlife, it remains poorly understood how the environment shapes most host–pathogen systems. Here, we employ a three‐step framework to study microclimate influence on ectotherm host thermal behaviour, focusing on amphibian chytridiomycosis in fire salamanders ( Salamandra salamandra ) infected with the fungal pathogen Batrachochytrium salamandrivorans ( Bsal ). Laboratory trials reveal that innate variation in thermal preference, rather than behavioural fever, can inhibit infection and facilitate salamander recovery under humidity‐saturated conditions. Yet, a 3‐year field study and a mesocosm experiment close to the invasive Bsal range show that microclimate constraints suppress host thermal behaviour favourable to disease control. A final mechanistic model, that estimates range‐wide, year‐round host body temperature relative to microclimate, suggests that these constraints are rule rather than exception. Our results demonstrate how innate host defences against epizootics may remain constrained in the wild, which predisposes to range‐wide disease outbreaks and population declines. Abstract : While epizootics increasingly affect wildlife, it remains poorly understood how the environment shapes most host–pathogen systems. Here, we employ a three‐step framework composed of laboratory experiments, fieldwork and mechanistic modelling to study how microclimate steers the ability of fire salamanders to counter the fungal pathogen Batrachochytrium salamandrivorans ( Bsal ) through thermal behaviour. Our results demonstrate how host innate defences against epizootics may remain constrained in the wild, which predisposes to range‐wide disease outbreaks and population declines.